José Carlos Mariátegui's unfinished revolution : politics, poetics, and change in 1920s Peru - Moore, Melisa, 1969- (Bucknell University Press ; The Rowman & Littlefield Pub. Group, Inc., 2013)
This monograph on José Carlos Mariátegui, the seminal Latin American Marxist theorist, provides original readings of key writings through the lens of his understudied poetics, illuminating their full political meaning and impact. It offers insightful critiques of overlooked intellectuals, especially female, whom he championed. These readings are fully contextualized through comprehensive study of complex sociopolitical conditions and backgrounds, providing new thinking on Mariátegui, his contemporaries and Peruvian modernity that will benefit academics and students today.